Design Optimization And Characterization Of White Light For Led Street Light Application - Ying, Jocelynn Kee Xiao (2022)
The aim of this study was to evaluate the effects of lens type and shape on the light performance from surface mounted device light emitted diode (SMD LED) street light. Another factor considered was the influence of various shapes of the light emitting surface (LES) on the SMD LEDs and size of the SMD LED on light distribution. Besides, the effects of varying correlated colour temperature (CCT) of the LEDs were also investigated. Optical characterization was carried out using the Goniophotometer (GO-2000) and Integrating Sphere (PCE-200A). DIALux Evo software was used to perform the simulation. Road parameters, such as pole distance of 35 m and pole heights of 8 m on a 7 m width road were used. The road requirement was according to the Tenaga Nasional Berhad (TNB), whereby the street lights must comply with ME4A road classification requirements. The findings showed that Lens E demonstrated a better light performance as compared to Lens A, Lens B, Lens C and Lens D, owing to the rectangular shape of Lens E. The smaller shape of the rectangular lens with classification of Type II-M has lesser light pollution problems. A study comparison between the different CCTs was conducted. Warm White was selected for further investigation into the different shape and size of SMD LEDs as well as key colour for colour mixing.